2015
DOI: 10.1007/s40735-015-0027-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Electrochemical Synergism of API X42 Pipeline Steel During Erosion–Corrosion

Abstract: Hydro-transportation is an economic and flexible way to transport natural resources such as oil and gas from excavation to the extraction plants, refineries, and consumer-ready products to markets. However, interaction between solid particles, corrosive fluid, and target material often results in significant mutual reinforcement due to the combined action of erosion and corrosion. In this study, erosion-corrosion behavior of API pipeline steel has been assessed in 2 g l -1 NaCl solution purged with CO 2 as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 89 publications
1
3
0
Order By: Relevance
“…This result is consistent with the findings reported by the other previous studies [26]. It is reported that the maximum E-C rate were obtained with impact angle ranges from 30 • to 50 • for a range of materials such as pure iron, 304 stainless steel and aluminum [26][27][28][29]. The lowest values of weight loss due to E-C were recorded at an impacting angle of 90 • .…”
Section: Effect Of Ecap On Erosion-corrosion At Different Impacting Asupporting
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with the findings reported by the other previous studies [26]. It is reported that the maximum E-C rate were obtained with impact angle ranges from 30 • to 50 • for a range of materials such as pure iron, 304 stainless steel and aluminum [26][27][28][29]. The lowest values of weight loss due to E-C were recorded at an impacting angle of 90 • .…”
Section: Effect Of Ecap On Erosion-corrosion At Different Impacting Asupporting
confidence: 92%
“…The previous researchers found that the material loss due to E-C is mainly affected by experiment duration, slurry flow velocity, impacting angle, erodent particle size, and solid particles concentration [27][28][29][30][31][32][33]. It is reported that the combined effect of erosion and corrosion together represents almost 40 -60% of the total weight loss [34].…”
Section: Introductionmentioning
confidence: 99%
“…The impacting particle energy is directly proportional to the velocity. Therefore, as the flow rate increased the wear rates increase [33].…”
Section: Role Of Sandmentioning
confidence: 98%
“…Synergism of erosion and corrosion can result in more significant material loss than that caused individually [4,6,7]. Several investigations [8][9][10] have been reported to study the erosion-corrosion phenomena involved.…”
Section: Introductionmentioning
confidence: 99%